Pattern recognition : 11th Mexican Conference, MCPR 2019, Querétaro, Mexico, June 26-29, 2019, Proceedings /: 11th Mexican Conference, MCPR 2019, Querétaro, Mexico, June 26-29, 2019, Proceedings. (2019) - Unknown
No abstract available